Pemuda cinta tanah air : wacana pemuda Indonesia dalam bingkai Nasionalisme - Pemuda cinta tanah air : wacana pemuda Indonesia dalam bingkai Nasionalisme (Matapena Institute, 2011)
Risma,1/ dandy, c.1